2003
DOI: 10.1097/00008390-200302000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized multicentre phase III trial of fotemustine plus whole brain irradiation versus fotemustine alone in cerebral metastases of malignant melanoma

Abstract: The main objective of this prospective multicentre randomized phase III study was to compare a combined regimen of fotemustine plus whole brain irradiation with fotemustine alone in terms of cerebral response and time to cerebral progression in patients with melanoma cerebral metastases. Seventy-six patients were randomized to receive either fotemustine (arm A, n = 39) or fotemustine plus whole brain irradiation (arm B, n = 37). Fotemustine was administered intravenously at 100 mg/m(2) on days 1, 8 and 15, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
58
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 18 publications
0
58
0
8
Order By: Relevance
“…A study of temozolomide with WBRT for MMM in 31 patients has shown a median survival of 6 months, a CR in only one patient and PR in only two patients leading the authors to conclude that WBRT has a lower than expected activity . A recent French randomised phase III trial in 76 patients showed that fotemustine plus WBRT delayed the time to brain tumour progression compared to fotemustine alone, but without significant improvement in terms of objective control or overall survival (Mornex et al, 2003).…”
mentioning
confidence: 99%
“…A study of temozolomide with WBRT for MMM in 31 patients has shown a median survival of 6 months, a CR in only one patient and PR in only two patients leading the authors to conclude that WBRT has a lower than expected activity . A recent French randomised phase III trial in 76 patients showed that fotemustine plus WBRT delayed the time to brain tumour progression compared to fotemustine alone, but without significant improvement in terms of objective control or overall survival (Mornex et al, 2003).…”
mentioning
confidence: 99%
“…Эффективность химиотерапии в чистом виде и ее комбинаций с лучевой терапией (ЛТ) не превышала 7-10% без существенного влияния на общую выживаемость (табл. 2) [11][12][13][14]. Среди возможных причин, объясняющих низкую эффектив-ность лечения, приводятся: недостаточная степень проникнове-ния через ГЭБ, активное выведение препарата при помощи эф-флюксных насосов (drug efflux pumps), химиорезистентность, за-щита астроцитов от апоптоза, вызываемого химиопрепаратами с помощью паракринной регуляции и др.…”
unclassified
“…[13] Темозоломид + ЛТ на головной мозг 31 9,7 F. Mornex и соавт. [14] Фотемустин 39 7,4 F. Mornex и соавт. [14] Фотемустин + ЛТ на головной мозг 37 10 В 2014 г. R. Dummer и соавт.…”
unclassified
See 1 more Smart Citation
“…Trials of a related compound, fotemustine, have reported response rates of 5 -25% in melanoma metastatic to the brain (Jacquillat et al, 1990;Mornex et al, 2003;Avril et al, 2004) and fotemustine has also been given in combination with dacarbazine Merimsky et al, 1992;Lee et al, 1993;Chang et al, 1994;Comella et al, 1997;Richard et al, 1998;Seeber et al, 1998) and with temozolomide (Marzolini et al, 1998;Gander et al, 1999). These drug combinations are generally well tolerated although unexpected pulmonary toxicity was reported in two studies of the combination of dacarbazine and fotemustine (Gerard et al, 1993;Lee et al, 1993).…”
mentioning
confidence: 99%